2005
DOI: 10.1128/ec.4.11.1765-1774.2005
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Cell Death in Podospora Autophagy Mutants

Abstract: Although autophagy is characteristic of type II programmed cell death (PCD), its role in cell death is currently debated. Both cell death-promoting and prosurvival roles of autophagy have been reported depending on the organism and the cell type. In filamentous fungi, a cell death reaction known as an incompatibility reaction occurs when cells of unlike genotype fuse. Cell death by incompatibility is characterized by a dramatic vacuolar enlargement and cell lysis. In Podospora anserina, autophagy is induced ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
123
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 53 publications
9
123
0
2
Order By: Relevance
“…Null mutants of the idi-7/PaATG8 gene (the orthologue of S. cerevisiae ATG8) form fewer aerial hyphae and no protoperithecia (27). Furthermore, a null mutant of PaATG1 (the orthologue of S. cerevisiae ATG1) shows the same defects as those of the ⌬idi-7/PaATG8 mutants (26). However, studies on autophagy and the identification of the genes involved have not been reported in deuteromycetes.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Null mutants of the idi-7/PaATG8 gene (the orthologue of S. cerevisiae ATG8) form fewer aerial hyphae and no protoperithecia (27). Furthermore, a null mutant of PaATG1 (the orthologue of S. cerevisiae ATG1) shows the same defects as those of the ⌬idi-7/PaATG8 mutants (26). However, studies on autophagy and the identification of the genes involved have not been reported in deuteromycetes.…”
mentioning
confidence: 94%
“…Additionally, in Caenorhabditis elegans, atg mutations result in abnormal dauer development, which is also induced by starvation, overcrowding, high temperature and so on (17). Recent studies have suggested that autophagy might participate in diseases such as cancer, liver disease, muscular disorder, and neurodegeneration (31) and protect from infection by bacterial pathogens (e.g., group A Streptococcus and Shigella) (20,22).In filamentous fungi, the processes of autophagy have been observed and studied for Podospora anserina (26,27). In this species, autophagy is induced during cell death by incompatibility, which occurs when cells of different genotypes fuse.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative hypothesis is that PCD by incompatibility is similar to Type II PCD or autophagy, where cells undergoing autophagy display morphological features such as vacuolization and cell lysis (Marek et al, 2003;Pinan-Lucarré et al, 2003;Pinan-Lucarré et al, 2007). Although both types of cell death could be involved in this process, autophagy has been suggested as merely a consequence of PCD by incompatibility and that it does not represent an actual mechanism of PCD (Pinan-Lucarré et al, 2005). Thus, even though PCD associated with vegetative incompatibility represents one of the best studied forms of PCD in fungi, the exact mechanism of how cell death by incompatibility is activated remains unclear.…”
Section: Introductionmentioning
confidence: 99%